A REVISION OF AESCHYNANTHUS (GESNERIACEAE) IN CAMBODIA, LAOS AND VIETNAM - Middleton, D. J. (Edinburgh Journal of Botany, 2009)
The species of Aeschynanthus Jack (Gesneriaceae) in Cambodia, Laos and Vietnam are revised. Eighteen species are recognised, keys to the species are given, all names are typified, and detailed descriptions of all species are provided. Conservation assessments are given for all species. Aeschynanthus cambodiensis D.J.Middleton, Aeschynanthus jouyi D.J.Middleton and Aeschynanthus pedunculatus D.J.Middleton are newly described.
Keywords: Aeschynanthus; Cambodia; Gesneriaceae; Laos; taxonomic revision; Vietnam